Answer
a)
$y=(x+1)^{2}$
$x \gt -1$
b)
As $t$ increases, $x$ also increases.
So the arrow should be pointing in the direction in which x increases.
There should be a hole at $(-1,0)$.
![](https://gradesaver.s3.amazonaws.com/uploads/solution/beddc665-9890-4df5-a018-db7a1eb342e9/result_image/1513496195.png?X-Amz-Algorithm=AWS4-HMAC-SHA256&X-Amz-Credential=AKIAJVAXHCSURVZEX5QQ%2F20250215%2Fus-east-1%2Fs3%2Faws4_request&X-Amz-Date=20250215T142250Z&X-Amz-Expires=900&X-Amz-SignedHeaders=host&X-Amz-Signature=6a31dbc75bb49534686d16e92495df4714cbefa8e24bf58db4dc8f1b5abc1716)
Work Step by Step
a)
Given that $x=e^{t}-1$
$x+1=e^{t}$
Also given that $y=e^{2t}$
we can write as $y=(e^{t})^{2}$
Use the first equation to replace $e^{t}$ with $x+1$
$y=(x+1)^{2}$
(After graphing)
Domain: $x \gt -1$
Range: $y \gt 0$
b)
we know that
$y=(x+1)^{2}$
where
$x \gt -1$
Given that $x=e^{t}-1$
As $t$ increases, $x$ also increases.
So the arrow should be pointing in the direction in which x increases.
There should be a hole at $(-1,0)$.